I HAVE A LETTER TO MY MATH TEACHERS: A QUALITATIVE STUDY WITH GIFTED STUDENTS - Çalışkan Toraman, Çiğdem; Toraman, Çetin (International Online Journal of Education and Teaching, 2025)
This research aimed to explore the experiences and phenomenological aspects of gifted students' participation in mathematics classes at a science and arts center (a gifted education center in Turkey). This phenomenological study involved 47 students aged 8-15. Data were collected through letters written by the students to their mathematics teachers and analyzed using phenomenological and inductive content analysis. The findings revealed the overarching theme: "My Mathematical Course". Under this theme, students' perceptions of mathematics as a space of freedom/place of self-discovery and, conversely, as a source of boredom were identified. Furthermore, the students expressed expectations and desires regarding the mathematics class, the science and arts center, the system, and their teachers. The findings are discussed within the broader context of the literature.